Trade-offs in CO 2-oriented Vehicle Tax Reforms: a Case Study of Greece - Adamou, Adamos; Clerides, Sofronis; Zachariadis, Theodoros (My University, 2012)
We estimate demand for automobiles in Greece using a model of product differentiation and use the model to evaluate carbon-based tax schemes that could shift consumer purchases towards low CO2 emission cars. We find that careful policy design, supported by appropriate modeling, can bring about substantial environmental benefits without losing control of economic parameters such as public finances or firm profits. This contrasts to the results of recent vehicle tax reforms in European countries, which turned out to be more costly than initially expected.
Keywords: Automobiles--Motors--Exhaust gas; Carbon taxes; Purchasing; Carbon dioxide